Protocol for a cluster randomised controlled trial of an intervention to improve the mental health support and training available to secondary school teachers – the WISE (Wellbeing in Secondary Education) study. (December 2016) - Kidger, Judi; Evans, Rhiannon; Tilling, Kate; Hollingworth, William; Campbell, Rona; Ford, Tamsin; Murphy, Simon; Araya, Ricardo; Morris, Richard; Kadir, Bryar; Moure Fernandez, Aida; Bell, Sarah; et al.
Abstract Background Teachers are reported to be at increased risk of common mental health disorders compared to other occupations. Failure to support teachers adequately may lead to serious long-term mental disorders, poor performance at work (presenteeism), sickness absence and health-related exit from the profession. It also jeopardises student mental health, as distressed staff struggle to develop supportive relationships with students, and such relationships are protective against student depression. A number of school-based trials have attempted to improve student mental health, but these have mostly focused on classroom based approaches and have failed to establish effectiveness. Only a few studies have introduced training for teachers in supporting students, and none to date have included a focus on improving teacher mental health. This paper sets out the protocol (version 4.4 20/07/16) for a study aiming to address this gap. Methods Cluster randomised controlled trial with secondary schools as the unit of randomisation. Intervention schools will receive: i) Mental Health First Aid (MHFA) training for a group of staff nominated by their colleagues, after which they will set up a confidential peer support service for colleagues ii) training in MHFA for schools and colleges for a further group of teachers, which will equip them to more effectively support student mental health iii) a short mental health awareness raising session and promotion of the peer support service for all teachers. Comparison schools will continue with usual practice. The primary outcome is teacher wellbeing measured using the Warwick Edinburgh Mental Wellbeing Scale (WEMWBS). Secondary outcomes are teacher depression, absence and presenteeism, and student wellbeing, mental health difficulties, attendance and attainment. Measures will be taken at baseline, one year follow up (teachers only) and two year follow up. Economic and process evaluations will be embedded within the study. Discussion This study will establish the effectiveness and cost-effectiveness of an intervention that supports secondary school teachers' wellbeing and mental health, and improves their skills in supporting students. It will also provide information regarding intervention implementation and sustainability. Trial registration International Standard Randomised Controlled Trial Number:ISRCTN95909211 registered 24/03/16